Perancangan Sistem Bot Alert Telegram Sebagai Notifikasi Deteksi Serangan Ping of Death Berbasis Snort - Rachman Juliandi, Dicky; Karman, Joni; Rusdiyanto (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
The Ping of Death attack is a type of denial of service (DoS) attack that exploits a vulnerability in the Internet Control Message Protocol (ICMP). This attack is carried out by sending a large number of pings that exceed the maximum limit allowed by the network, causing the server or network device to become slow or even unresponsive. This attack can have a severe impact on server and network performance, especially for services that require high availability such as the Sinanan Lubuklinggau server. This research aims to design a Telegram Bot alert system as an automatic notification tool to detect Ping of Death attacks on the Sinanan Lubuklinggau server, using Snort, a detection system software that is infiltrating the "NIDS" network. Snort is used to detect attacks by examining data packets passing through the network. If Snort detects suspicious activity such as a Ping of Death attack, the system will immediately send an alert via the Telegram bot. The alert contains detailed information about the attack, including the IP address, attacker, timestamp, and location of the affected network. This system has also been proven to work well in high-traffic network environments without disrupting server performance. By implementing this system, network administrators can act more quickly to prevent and manage the threat of Ping of Death attacks, thereby maintaining the stability and security of the Sinanan Lubuklinggau server.